Holothuroid Species in Talikud Island, Island Garden City of Samal (IGaCoS) - Tubal, Karla B.; del Rosario, Bernadette I. (JPAIR Multidisciplinary Research, 2008)
The study titled "Holothuroid Species in Talikud Island, Island Garden City of Samal (IGaCoS)" aimed to identify holothuroid species present in the area using ossicle-based taxonomic keys and to determine their distribution across ten stations while considering prevailing environmental conditions. A descriptive approach was employed to document the taxonomic account and distribution of holothuroids in ten selected areas of Talikud Island: Dodaron, Baybay, Maniksik, Unosutan, Tastas, Mansod, Cogon, Dapia Baybay, and Kamaonan. The study identified 15 species belonging to three families: Synaptidae (Synapta maculata, Polyplectana kefersteini, Opheodesoma sp.), Stichopodidae (Thelenota sp., Stichopus sp., Stichopus horrens), and Holothuriidae (Pearsonothuria graeffei, Holothuria hilla, Holothuria pulla, and six unidentified Holothuria species). Human activities in certain areas were found to reduce holothuroid diversity and numbers. The findings highlight the importance of sustainable practices to conserve holothuroid populations in Talikud Island.